Protean career orientation, vocational identity, and self-efficacy: an empirical clarification of their relationship. Issue 2 (4th March 2017) - Hirschi, Andreas; Jaensch, Vanessa K.; Herrmann, Anne
ABSTRACT: There is a large interest in how people can be more protean in their career development, exhibiting a self-directed striving for personally valued career outcomes. However, existing research on the protean career needs to better address issues of antecedents and outcomes as well as unique effects of a protean career orientation (PCO). We present two studies investigating how PCO is related to vocational identity clarity and occupational self-efficacy. Study 1 reports a 1-year, three-wave cross-lagged study among 563 university students and established that PCO preceded changes in identity and self-efficacy—but not the other way around. A 6-month longitudinal study of 202 employees, Study 2 showed that identity clarity and self-efficacy mediated the effects of PCO on career satisfaction and proactive career behaviours. PCO only possessed incremental predictive validity regarding proactive career behaviours. However, we could not confirm specific direct or mediated effects of PCO on job satisfaction. These results imply that PCO is closely related to vocational identity clarity and self-efficacy because it enhances these career attitudes. Moreover, identity and self-efficacy mediate some, but not all of the effects of PCO on important career outcomes.